Pengaruh Persistensi Laba, Book Tax Different, dan Struktur Modal Terhadap Earning Response Coefficient - Arnetta Valencia Qoys; Dirvi Surya Abbas; Mulyadi Mulyadi (International Forum of Researchers and Lecturers, 2023)
The purpose of this study is to determine the effect of profit persistence, book tax differences, and capital structure on the earnings response coefficient in property and real estate sector companies listed on the Indonesia Stock Exchange (IDX). The research time period used is 5 years, namely the period 2018-2022. The sampling technique uses purposive sampling technique. Based on the established criteria, 13 companies were obtained. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analysis method used is panel data regression analysis. The results showed that Profit Persistence influences the Earning Response Coefficient. Book Tax Different and Capital Structure have no effect on the Earning Response Coefficient.